Analisis Komparasi Cycles X Render Dan Cycles Render Menggunakan Google Colab - T. Rafli Abdillah (Jurnal Tika, 2023)
A good and fast rendering engine is needed in the world of 3D rendering. In this article, we perform a comparative analysis between two popular rendering engines, Cycles X and Cycles using Google Colab. Google Colab is a free platform that can be used to access the rendering engine on a remote server with GPU access. In this study, we use the same object files and settings on both render engines to compare render times and render quality. The test results show that Cycles X is faster than Cycles in rendering 3D objects with the same resolution. However, Cycles X requires more complex settings and requires a more sophisticated GPU to produce optimal results. In conclusion, Cycles X can be a good choice for users who need high render speeds, while Cycles is still a solid choice for better render quality. Google Colab is a very useful and free tool to compare the performance of different rendering engines at a higher level.